Optimization of mixing parameters on techno-functional properties of fenugreek gum-soy protein isolate dispersion - Ibrahim, Nor Hayati; Huzaini, Aina Nabihah; Mohd Isa, Nor Suaidah; Abdul Hadi, Nabilah; Mustapha, Nor Afizah (Persatuan Biologi Gunaan Malaysia,Malaysian Society of Applied Biology, 2022)
Fenugreek (Trigonella foenum-graecum L.) gum (FG) has been identified as a hydrocolloid, with promising emulsifying and stabilizing properties. In an emulsion-based food system, these properties dramatically increased when FG was mixed with soy protein isolate (SPI). Nevertheless, it is highly dependent on mixing parameters such as FG:SPI ratio, pH, and temperature, and it is currently not well understood. The objective of this study was to determine the effects of FG:SPI ratio (3:1 - 1:1), pH (3 - 9), and temperature (65 - 85 °C) on techno-functional properties (flow properties, emulsifying properties, and turbidity) of the FG-SPI dispersion, to reveal the optimum mixing parameters. A response surface regression modeling demonstrated that the quadratic effect of the FG:SPI ratio had significantly (p<0.05) increased the flow properties of the dispersion. However, the interaction between FG:SPI ratio and temperature or pH gave the opposite effect. The FG:SPI ratio had the most significant (p<0.05) increasing effect on both emulsifying properties and turbidity. Conversely, the emulsifying properties were determined to decrease with the interaction effect of FG:SPI ratio and pH. The optimized mixing parameters were recorded at FG:SPI ratio of 2.6:1, pH of 3.0, and temperature of 70 °C, with apparent viscosity (0.19 Pa.s), emulsion stability (100%), and turbidity (2.91, Abs600) values were within the predicted ranges. The present findings provide an excellent opportunity to advance the use of FG-SPI dispersion in related to emulsion-based food products.